Meningkatkan Pemahaman Membaca Siswa Dengan Menggunakan Teknik Diagram Flowchart - Dahlina, Ulinuha (JEDLISH : Journal Of Education and English Language Teaching, 2021)
This research is aimed at improving the eighth grade students’ reading comprehension ability using diagrammatic flowchart at SMPN 3 Kramatwatu in the academic year of 2018/2019. This action research was conducted in two cycles. The researcher worked collaboratively with the English teacher and the eighth grade students of SMPN 3 Kramatwatu. The data of this study were qualitative and quantitative. The qualitative data were obtained through observation in the teaching and learning process during the implementation of the actions, interviews with the students and the English teacher about the implemented actions, and discussion with the English teacher as the collaborator. The qualitative data were in the forms of field notes and interview transcripts. Meanwhile, the quantitative data were collected through the pre-test and post-test. Therefore, the data were in the form of students’ reading scores in the pre-test and post-test. The results show that there are some improvements on the students’ reading comprehension ability. They make a good improvement in some aspects of reading skills such as guessing, and predicting. The improvement is also shown by the students’ positive behaviors toward the implementation of the diagrammatic flowchart related to their participation in the class and their interest in joining the activities. They are more active than before in every activity. They are active to participate in making prediction and guessing meaning. They are interested in reading the English texts and completing the tasks. The findings are supported by the result of the paired-samples t-test. On average, there is an improvement on students’ reading comprehension which is shown by the level of significant of the paired samples t-test 0,000, which means that there is a significant improvement of the students’ reading comprehension ability after the researcher implementing the diagrammatic flowchart.